A People Passing Rude British Responses to Russian Culture - Cross, Anthony (Open Book Publishers, 2012)
Described by the sixteenth-century English poet George Turbervile as "a people passing rude, to vices vile inclin'd", the Russians waited some three centuries before their subsequent cultural achievements-in music, art and particularly literature-achieved widespread recognition in Britain. The essays in this stimulating collection attest to the scope and variety of Russia's influence on British culture. They move from the early nineteenth century-when Byron sent his hero Don Juan to meet Catherine the Great, and an English critic sought to come to terms with the challenge of Pushkin-to a series of Russian-themed exhibitions at venues including the Crystal Palace and Earls Court. The collection looks at British encounters with Russian music, the absorption with Dostoevskii and Chekhov, and finishes by shedding light on Britain's engagement with Soviet film. Edited by Anthony Cross, one of the world's foremost authorities on Anglo-Russian relations, A People Passing Rude is essential reading for anyone with an interest in British and Russian cultures and their complex relationship.